Evaluation of plasma prealbumin as a novel inflammatory biomarker in dogs: a pilot study - Park, Sin-Wook; Kim, Keon; Kim, Ock-Kyu; Ro, Woong-Bin; Lee, Chang-Min (Frontiers in Veterinary Science, 2023)
Introduction Prealbumin (PAB) is a plasma protein synthesized in the hepatic parenchymal cells. PAB has a short half-life ( 2 days), and its concentration is affected by changes in transcapillary escape. Measurement of PAB is widely used in hospitalized patients in human medicine due to its decreasing concentration in states of inflammation and malnutrition. However, only a few studies are available in dogs. The aim of this study is to determine whether the plasma PAB concentration decreases in dogs with inflammation and to evaluate the relationship between the plasma PAB concentration and inflammation-related parameters in dogs. Methods A total of 94 dogs were divided into healthy (n = 33) and diseased (n = 61) groups. These were further divided into group A (n = 24) and group B (n = 37) according to plasma C-reactive protein (CRP) levels. Group A included dogs with a plasma CRP < 10 mg/L, and group B consisted of dogs with a plasma CRP ≥ 10 mg/L. Patient signalment, history, physical examination findings, hematologic and biochemical parameters, various inflammatory markers, and plasma PAB levels were investigated and compared between groups. Results The plasma PAB concentration was found to be lower in group B than in the other groups (p < 0.001), but no statistical difference was found when comparing the control group and group A (p > 0.05). A plasma PAB < 6.3 mg/dL predicted an increased CRP level (10 mg/L or greater) with a sensitivity of 89.5% and a specificity of 86.5%. Receiver operating characteristic curve analysis revealed that the area under the curve for PAB was higher than that for the white blood cell count, neutrophil count, albumin level, lactate level, neutrophil-to-lymphocyte ratio, and neutrophil percentage-to-albumin ratio. In addition, the PAB concentration was significantly negatively correlated with the CRP concentration (r = −0.670, p < 0.001). Conclusion In conclusion, this is the first study to demonstrate the clinical usefulness of the plasma PAB concentration as an inflammatory marker in dogs. These findings suggest that measuring the plasma PAB concentration along with the CRP concentration may be more useful for evaluating inflammation than measuring CRP alone in canine patients.